Dear Dad : growing up with a parent in prison--and how we stayed connected : a graphic memoir - Patton, Jay Jay; Valdez, Kiara (Graphix, an imprint of Scholastic ; Kaepernick Publishing, 2024)
"...Your dad is coming back home." As far back as nine-year-old Jay Jay Patton can remember, her dad, Antoine has been in prison. Growing up in Buffalo, New York with her mom and younger brother, she's only been to visit him twice. Instead, the two have sent each other numerous letters -- Jay Jay's letters can take weeks or months to reach her dad, and some never even get delivered. What's it going to be like having Dad home? This powerful coming-of-age graphic novel memoir tells Jay Jay Patton's life of growing up with a dad in -- and out of -- prison. How she and her dad were able to develop a powerful father/daughter bond and create Photo Patch -- a life-changing application that connects children to incarcerated parents. Because no child should have to grow up unable to engage with their parents. As Jay Jay says: "It's not a privilege for a kid to be able to talk to their parent. It's a right."--Publisher description.